Persistence of tall fescue in a subtropical environment : tiller survival over summer in response to ﬂowering control and nitrogen supply - Jauregui, José Martín; Michelini, D F.; Agnusdei, Monica Graciela; Sevilla, Gabriel Hipolito; Chilibroste, Pablo; Lattanzi, F.A.; Baudracco, Javier (Wiley, 2017)
Enhancing pasture persistence is crucial to achieve more sustainable grass-based animal production systems. Although it is known that persistence of perennial ryegrass is based on a high turnover of tillers during late spring and summer, little is known about other forage species, particularly in subtropical climates. To address this question, this study evaluated survival of grazed tall fescue tillers growing in a subtropical climate. We hypothesized that hard tactical grazing during winter to remove reproductive stems (designated as ‘flowering control’), and nitrogen fertilization in spring, would both improve tiller survival over summer, and thus enhance tiller density. This was assessed in two experiments. In both experiments, few tillers appeared during late spring and summer and so tiller density depended on the dynamics of vegetative tillers present in the sward in spring. In Experiment 2, flowering control and nitrogen fertilization both enhanced the survival of that critical tiller cohort, but the effects were not additive. Responses were similar but not statistically significant in Experiment 1, which had a warmer, drier summer and lower overall survival rates. Unlike grasses in temperate environments, persistence of tall fescue in this subtropical site appeared to follow a ‘vegetative pathway’; i.e., new tillers were produced largely in autumn, from vegetative tillers that survived the summer.